Sodium and Its Role in Cardiovascular Disease – The Debate Continues - Kong, Yee Wen; Baqar, Sara; Jerums, George; Ekinci, Elif I. (Frontiers in Endocrinology, 2016)
Guidelines have recommended significant reductions in dietary sodium intake to improve cardiovascular health. However, these dietary sodium intake recommendations have been questioned as emerging evidence has shown that there is a higher risk of cardiovascular disease with a low sodium diet, including in individuals with type two diabetes. This may be related to the other pleotropic effects of dietary sodium intake. Therefore, despite recent review of dietary sodium intake guidelines by multiple organizations, including the dietary guidelines for Americans, American Diabetes Association and American Heart Association, concerns about the impact of the degree of sodium restriction on cardiovascular health continue to be raised. This literature review examines the effects of dietary sodium intake on factors contributing to cardiovascular health, including left ventricular hypertrophy, heart rate, albuminuria, renin-angiotensin-aldosterone system activation, serum lipids, insulin sensitivity, sympathetic nervous system activation, endothelial function and immune function. In the last part of this review, the association between dietary sodium intake and cardiovascular outcomes, especially in individuals with diabetes, is explored. Given the increased risk of cardiovascular disease in individuals with diabetes and the increasing incidence of diabetes worldwide, this review is important in summarizing the recent evidence regarding the effects of dietary sodium intake on cardiovascular health, especially in this population.